An acidic heteropolysaccharide from Lycii fructus: Purification, characterization, neurotrophic and neuroprotective activities in vitro. (1st December 2020) - Zhang, Fang; Zhang, Xia; Guo, Sheng; Cao, Funing; Zhang, Xiaofei; Wang, Yaqi; Liu, Jiazheng; Qian, Bowen; Yan, Yichao; Chen, Peidong; Xu, Chunlei; Liu, Chunmei; et al.
Highlights: An acidic polysaccharide (LFP-1) was purified from Lycii fructus. LFP-1 contained arabinogalactans, homogalacturonan, rhamnogalacturonan moieties. LFP-1 exhibited neurotrophic at μg/mL levels in vitro on PC12 cells. LFP-1 had protective effect against MPP+ -induced neurotoxicity on PD model cells. Abstract: Regeneration of neurites network constitutes a neurotrophic and therapeutic strategy for Parkinson's disease (PD). Increasing evidence is supporting the potential application of natural polysaccharides in prevention or treatment of PD. In this study, an acidic heteropolysaccharide LFP-1 was isolated from Lycii fructus, and purified by ion-exchange and gel filtration chromatography. Structural features of LFP-1 were analyzed with molecular weight (MW) distribution, monosaccharide composition, methylation and nuclear magnetic resonance (NMR) spectra. LFP-1 was a complicated structured polysaccharide with an average MW of 1.78 × 10 4 Da and composed of highly branched arabinogalactans, homogalacturonan and rhamnogalacturonan moieties. LFP-1 promoted neuronal differentiation and neurite outgrowth in vitro in PC12 cell models. Furthermore, LFP-1 had a significantly protective effect against 1-methyl-4-phenylpyridiniumion (MPP+)-induced neurotoxicity in PD model PC12 cells. These observations unambiguously indicated the neurotrophic and neuroprotective activities of LFP-1, which may be developed for prevention or treatment of neurodegeneration in PD.